PENGARUH KONSENTRASI Azoksistrobin 250 g DAN RAK PENYIMPANAN TERHADAP LAMA PENYIMPANAN DAN MUTU BUAH MANGGAGEDONG GINCU - Syadudin Syadudin (Agroswagati Jurnal Agronomi, 2017)
Regency Cirebon have biggest contribution to West Java and sender represent one of fresh mango for the market of overseas. But on the other hand agribisnis mango still face the problem, especially in handling harvest to the end, where old strength keep still lower and still be found by disease Anthracnose (rotten of fruit).Bolt from the problem, research activity aimed at by use of depository fungsida rack and. To know the depository rack and concentration Azoksistrobin of  which influencing to depository duration  mango of gedong gincu.Analyse to use the experiment method with the complete random device and thrice restating, Data analysed by passing test F with the linear model. If result test the day-break of manner signifikan, continued its analysis use the Test of Bunch of Scott Knott at  real level  5 %. Result of statistical test show the : result of antecedent perception (supporter), indicating that analysis  quality of fruit (carbohydrate / rate of sugar and vitamin C) yielding quality of fruit do not differ the reality. second Supporter activity is measurement of temperature and dampness in each depository rack conducted every day, that is at morning and daytime of during 18 day .Analysis activity keep can be conducted by during four times yield the homogeneous treatment. After analysed, Bunch Scoot-Knott of  fourth, yielding value λ (lamda) more smaller than X2, hence fourth treatment have homogeneous. Thereby pursuant to result analyse the above, real different treatment to long keep is, treatment H, I, E and F.Result of perception of rate of sugar of mango gedong gincu before treatment (day to-0), showing influence which is not real. So also result of perception of sugar rate on to-7 yield the real influence treatment calculation. Later;Then result of last perception  also show the influence which is not real.Result of antecedent perception ( day to-0) to rate of vitamin C of at mango of gedong gincu, yielding influence calculation which is not real. So also result of analysis of rate of vitamin C on to-7 yield the calculation, remain to show the influence which is not real. Later;Then newly result of perception on to-14 ( last) of about rate of vitamin C, showing real influence.